Optimal Estimation of Population Mean in the Presence of Random Non-Response - Bhushan, Shashi; Pratap Pandey, Abhay (Thailand Statistician, 2023)
In the present paper, we have proposed some improved ratio and regression (or difference) type estimators of the finite population mean utilizing the information on auxiliary variables in the presence of random non-response. Using the Searls (1964) methodology, some improved ratio and regression (or difference) type estimators have been suggested in two different situations of random non-response and studied their properties. Proposed classes of estimators are empirically compared with some contemporary estimators of population mean under similar realistic conditions. Their performances have been demonstrated through numerical illustration followed by suitable recommendations.